2006
DOI: 10.1080/10550490500418997
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Withdrawal Among Non‐Treatment‐Seeking Adult Cannabis Users*

Abstract: This study investigates the clinical significance of a cannabis withdrawal syndrome in 104 adult, non-treatment-seeking, primarily cannabis users who reported at least one serious attempt to stop using cannabis. Retrospective self-report data were obtained on eighteen potential cannabis withdrawal symptoms derived from the literature, including co-occurrence, time course, and any actions taken to relieve the symptom. Study findings provide evidence for the clinical significance of a cannabis withdrawal syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
145
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(153 citation statements)
references
References 22 publications
(49 reference statements)
7
145
0
1
Order By: Relevance
“…These findings complement the growing body of literature supporting the existence of the cannabis dependence syndrome and cannabis withdrawal, as well as the validity of the DSM IV dependence criteria as they apply to cannabis dependence (Budney, 2006;Budney and Hughes, 2006). The findings of fair reliability for cannabis withdrawal criteria, despite the heterogeneity of the sample, complement recent findings showing that cannabis withdrawal is both clinically significant and readily identified even in non-treatment seeking populations (Copersino et al, 2006). Reliability estimates for stimulants and sedatives were less than satisfactory, similar to those reported for the SSAGA (Bucholz et al, 1995), perhaps due in both studies to the relatively low frequency of endorsement for criteria for these disorders.…”
Section: Discussionsupporting
confidence: 79%
“…These findings complement the growing body of literature supporting the existence of the cannabis dependence syndrome and cannabis withdrawal, as well as the validity of the DSM IV dependence criteria as they apply to cannabis dependence (Budney, 2006;Budney and Hughes, 2006). The findings of fair reliability for cannabis withdrawal criteria, despite the heterogeneity of the sample, complement recent findings showing that cannabis withdrawal is both clinically significant and readily identified even in non-treatment seeking populations (Copersino et al, 2006). Reliability estimates for stimulants and sedatives were less than satisfactory, similar to those reported for the SSAGA (Bucholz et al, 1995), perhaps due in both studies to the relatively low frequency of endorsement for criteria for these disorders.…”
Section: Discussionsupporting
confidence: 79%
“…These data support and converge with that from controlled laboratory studies to suggest the cannabis withdrawal syndrome experienced when frequent users of cannabis stop using cannabis has clinical importance. In addition, prior studies indicate that many cannabis users take direct action to relieve the distress experienced during abstinence, e.g., resume cannabis use or take other drugs (Coffey et al, 2002;Copersino et al, 2006), and the present study indicates that cannabis users clearly perceive that withdrawal symptoms negatively affect their desire and ability to quit. Group mean severity scores for the WDS (refer to Y-axis scale on left side of figure) and individual symptoms on the Withdrawal Symptom Checklist (refer to Y-axis scale on right side of figure).…”
Section: Discussionmentioning
confidence: 78%
“…Recent studies have provided growing support for the clinical importance of cannabis withdrawal. For example, the majority of adults and adolescents enrolled in outpatient treatment for cannabis dependence report having experienced withdrawal symptoms following a quit attempt, report difficulty achieving initial periods of abstinence, complain that withdrawal contributes to their inability to quit, and report using cannabis or taking other direct action to alleviate withdrawal symptoms (Budney, Novy, & Hughes, 1999;Budney, Radonovich, Higgins, & Wong, 1998;Coffey et al, 2002;Copeland, Swift, & Rees, 2001;Copersino et al, 2006;Crowley, MacDonald, Whitmore, & Mikulich, 1998;Stephens, Babor, Kadden, Miller, & the Marijuana Treatment Project Research Group, 2002;Vandrey, Budney, Moore, & Hughes, 2005).…”
mentioning
confidence: 99%
“…Of this sample, 65 % indicated that poor sleep was a primary symptom that led to their relapse [45]. Furthermore, in two studies of nontreatment-seeking cannabis users, 32-47 % reported poor sleep during a previous time of abstinence, and 48-77 % indicated that they had relapsed to cannabis use or increased the use of other substances in order to improve sleep quality [55,56].…”
Section: Sleep Disturbance Increases the Risk Of Cannabis Lapse/relapsementioning
confidence: 99%